PERANAN PENTING PERENCANAAN DAN PENGEMBANGAN KARIER - Nurmasari S.Sos., M.Si (UIR Press, 2018)
Planning and career development, a planning process that enables employees to identify sasaransasaran careers and pathways leading to goals / objectives are. Planning programs and career development provides the opportunity for employees to explore their interests, desires and their career options in the company, because it is through this process employees can look for ways to improve themselves in order to develop skills and the ability to achieve the targeted position. For that management must seriously take into-overdue and treating employees with respect to the potential for achievement. The use of directions and paths and career development process in accordance with the needs and interests of employees with the company towards mutual benefit. Process and career development should be able to provide certainty to employees more transparent and secure and be able to grow and develop all the skills, intellectual, wawasasan, motivation, and dedication of the employees on the job position that embrace. Through process and career development can be pursued coaching employees towards the right on the right place.